Developing intermediate machines for high-land agriculture. (2020) - Franco, Walter; Barbera, Filippo; Bartolucci, Luigi; Felizia, Tiziano; Focanti, Federica
Abstract: The article analyzes the role of appropriate technologies for mechanization and innovation in small-scale farming in the mountainous and hilly areas of Italy's Piedmont region. Our approach to appropriate technologies focuses on mountain farmers whose needs have not been met by advances in agricultural mechanization, which have largely served the interests of lowland agribusiness. Mountain farmers' technological needs were determined using a specific methodology based on an in-depth analysis of the reference target and a field work using an open and inclusive process. The needs thus identified served as the starting point for designing appropriate and intermediate machines. In the conclusions, we present some general implications of appropriate technologies in terms of co-design for development.